Regulation of Cartilage Development and Diseases by Transcription Factors - Nishimura, Riko (J Bone Metab, 2017)
Genetic studies and molecular cloning approaches have been successfully used to identify several transcription factors that regulate the numerous stages of cartilage development. Sex-determining region Y (SRY)-box 9 (Sox9) is an essential transcription factor for the initial stage of cartilage development. Sox5 and Sox6 play an important role in the chondrogenic action of Sox9, presumably by defining its cartilage specificity. Several transcription factors have been identified as transcriptional partners for Sox9 during cartilage development. Runt-related transcription factor 2 (Runx2) and Runx3 are necessary for hypertrophy of chondrocytes. CCAAT/enhancer-binding protein β (C/EBPβ) and activating transcription factor 4 (ATF4) function as co-activators for Runx2 during hypertrophy of chondrocytes. In addition, myocyte-enhancer factor 2C (Mef2C) is required for initiation of chondrocyte hypertrophy, presumably by functioning upstream of Runx2. Importantly, the pathogenic roles of several transcription factors in osteoarthritis have been demonstrated based on the similarity of pathological phenomena seen in osteoarthritis with chondrocyte hypertrophy. We discuss the importance of investigating cellular and molecular properties of articular chondrocytes and degradation mechanisms in osteoarthritis, one of the most common cartilage diseases.